17
It is an equation and the value of m is -6
2m + 2 = 3m + 4 => 2m-3m = 4-2 => -m = 2 => m= -2
-3m + 8 = 2 -3m = 2 - 8 -3m = -6 m = -6/-3 m = 2
3m + 7 = 5 Subtract 7 from both sides: 3m = -2 Divide both sides by 3: m = -2/3
17
It is an equation and the value of m is -6
2m + 2 = 3m + 4 => 2m-3m = 4-2 => -m = 2 => m= -2
-3m + 8 = 2 -3m = 2 - 8 -3m = -6 m = -6/-3 m = 2
3m+2=17 First, subtract 2 to get m on one side. 3m+2-2=17-2 3m=15 Divide by 3 to get m by itself. 3m/3=15/3 m=5 m equals 5.
3m + 7 = 5 Subtract 7 from both sides: 3m = -2 Divide both sides by 3: m = -2/3
m(3m + 2)
Without any equality signs the given terms can't be classed as equations.
To solve the equation 5m + 3 = 3m + 9, you need to isolate the variable m. Start by subtracting 3m from both sides to get 2m + 3 = 9. Then, subtract 3 from both sides to get 2m = 6. Finally, divide by 2 to find m = 3.
2
2 - 3m + 7 = 4m - 9 - m - 28 46 = 6m 46/6 = 23/3 = 7.6666 = m
5m+3=3m+9 First get the ms and the constants on separate sides. Do this by subtracting 3 from both sides (5m=3m+6) Then subtract 3m from both sides (2m=6) then divide both sides by 2 to find m. (m=3)